Determınan Manajemen Laba: Fınancıal Leverage, Profıtabılıtas, dan Karakterıstık Perusahaan - Ellysia Millenia; Tjhai Fung Jin (Jurnal Bisnis dan Akuntansi, 2021)
The objective of this research is to obtain empirical evidence about the effect of firm size, financial leverage, firm age, audit quality, audit committee size, board size, managerial ownership, institutional ownership, profitability, and firm growth on earnings management. The research sample consisted of 122 non-financial companies listed on the Indonesia Stock Exchange during 2017-2019 with 366 data tested using the multiple regression method. The results showed that financial leverage and firm growth have effect on earnings management. On the other hand, firm size, firm age, audit quality, audit committee size, board size, managerial ownership, institutional ownership, and profitability do not show any effect on earnings management.